Micro- and macro-porosity of dry- and saturated-state recycled aggregate concrete. (20th February 2019) - Thomas, C.; Setién, J.; Polanco, J.A.; de Brito, J.; Fiol, F.
Abstract: Society is becoming aware of the environment and progressively using more recycled aggregates to produce recycled structural aggregate concrete. In addition, many researches have analysed the properties of hardened recycled aggregate concrete, but few of them have focused on the mixing method and the consequences that it has on the properties of concrete. In this research, recycled aggregate concrete using dry, with extra water supply, and saturated recycled aggregate has been prepared. The different mixing conditions induce differences the micro and macroporosity of concrete that have been evaluated by computerized axial tomography, scanning electron microscopy and a new developed methodology, based on digital image analysis, developed to analyse the distribution and size of macroporosity. The software has been implemented in Matlab © and is available to the readers of the journal for downloading and use. The results show that the dry and saturated recycled aggregate lead to very different concrete properties. On the one hand, the use of dry aggregate causes a local reduction of the w/c ratio, increasing heterogeneity and decreasing workability. On the other hand, the saturated aggregate incorporates extra water by adsorption that causes an increase in the water/cement ratio, thus increasing the porosity volume and size of the new mortar of the recycled aggregate concrete.